Health problems in geriatric population of age group ≥70 years in rural Kerala, India: a cross sectional study - M., Sarin S.; K., Jayasree A. (International Journal of Research in Medical Sciences, 2019)
Background: The proportion of elderly population is increasing considerably world over. The health and socio-economic issues of this section is to be considered separately and in depth insights about them is needed for formulating elderly friendly health policy. This study intends toidentify the important health concerns of elderly population above the age group of 70 years in a rural area in North Kerala, India. Methods: It is a community based cross-sectional descriptive study involving all individuals above the age group of 70 years in a randomly selected panchayath ward from rural North Kerala. The data regarding demography, socioeconomic aspects, medical history, access to health care and treatment of chronic illnesses were collected through interview of study participants by a trained health care volunteer using a pre-validated questionnaire. Results: A total of 93 individuals above the age group of 70 years were included in the study out of which 63% were females and 37% males. In the study population 55.9% of the elderly were widowed and 87.1 % were staying along with their children. Almost 75% of the elderly received social welfare pension from government agencies and 14.3% received service pensions. 67.74% of the study population were hypertensive and 35.56% were diabetic. Other health issues included arthritis, coronary artery disease, chronic kidney disease, genito urinary symptoms and cerebrovascular accident. Conclusion: The study provide valuable insights into the health and social issues of elderly in Kerala and points to the importance of formulating an elderly friendly health policy in the state.